The Perspective of the Wangi-Wangi Community on Agriculture in the Oral Tradition of Kaƃanti Lullabies - Hamiruddin Udu; Hidrawati Hidrawati (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
The oral tradition of kaƃanti pengantar tidur (lullaby kaƃanti) is a cultural expression of the Wangi-Wangi community, functioning not only as a medium to lull children to sleep but also as a vehicle for transmitting life values. This study aims to explain the representation of agriculture in the oral tradition of kaƃanti lullabies in the Wangi-Wangi community, identify and analyze the metaphors used to describe aspects of agriculture, and interpret the cultural meaning of these metaphors within the context of the Wangi-Wangi community's cultural perspective. Using a qualitative descriptive approach and ethnolinguistic methods, data were collected through observation, in-depth interviews, documentation, and textual analysis of kaƃanti songs. The findings reveal that kaƃanti contains various agricultural metaphors that reflect the worldview of an agrarian society, such as metaphors related to fertility, life cycles, productive age, and the value of hard work. Agricultural symbols are represented through depictions of the body, plants, and crops, emphasizing the deep connection between humans and nature. These results confirm that kaƃanti carries not only aesthetic value but also functions as a medium for social reflection and meaning-making in the local Wangi-Wangi culture. This study recommends preserving kaƃanti as a cultural heritage and a valuable source of education based on local wisdom.